4th party logistics service providers and industrial cluster competitiveness - Subramanian, Nachiappan; Papadopoulos, Thanos; Gunasekaran, Angappa; Nie, Pie (Emerald, 2016)
Purpose – Firms within industrial clusters are subject to challenges such as globalization, limited resources, volatility of international markets and financial instabilities. 4th party logistics (4PL) service providers are supporting individual firms to overcome such challenges by using collaborative operational capabilities from within an industrial cluster to their enhance competitiveness. The purpose of this paper is to focus on China and proposes a collaborative operational capabilities framework to illustrate the role of 4PL in industrial cluster competitiveness.